Keputusan Konsumen Memilih Jasa Transportasi Online - Nirmala Nirmala; Mayla Surveyandini (FEB UNWIKU PURWOKERTO, 2020)
Online transportation services are an option because they are considered capable of providing a greater customer value than other conventional transportation services. This study aims to partially analyze the significance of the influence of the factors of ease, safety and efficiency factors that influence citizen decisions in Banyumas in choosing online transportation services. The research sample amounted to 100 people based on the accidental sampling method. This study uses a multiple linear regression analysis tool. The results showed the multiple linear regression equation Y = 5,159 + 0,030X1 + 0,263X2 + 0,455X3 + e and the coefficient of determination equal to 0,368. From the F test results it was found that the value of Ftest> Ftable(21,134 > 3,09), so that the model was declared feasible. From the results of the t test obtained the second and third hypotheses were accepted, while the first hypothesis was rejected. This means that the safety and efficiency factors have a significant effect while the ease factor did not have a significant influence on the decisions of the people in Banyumas in choosing online transportation services